Reciprocal translocation with adaptive segment length - Acan, A (IEEE, 2002)
A novel artificial crossover operator based on reciprocal translocation of chromosomal segments is introduced. Positions and lengths of genome segments are determined at random. However, segment size limits are adaptively changed based on the improvement of average fitness value over generations. The implementation results for difficult problems are very encouraging.
IEEE World Congress on Computational Intelligence (WCCI2002) -- MAY 12-17, 2002 -- HONOLULU, HI